Literature Review: Relationship of Chronic Disease Management Program (Prolanis) To Blood Pressure of Hypertension Patients - Lisa Fitriani; Muhammad Irwan Setiawan; Anggun Wulandari; Meitria Syahadatina Noor; Nita Pujianti (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
Prolanis is a program to improve the quality of life, health status, and optimal life expectancy. The program is called to be good if it can improve the quality of life and health status of the prolanis participants, the program activities are medical/educational consultations, home visits, reminder, and prolanis gymnastics. This research aims to explain the relationship of chronic disease management program (prolanis) to blood pressure of hypertension patients. This research is based on a literature review with Scoping Review method. Research articles were obtained through Google Scholar and DOAJ with 10 articles results that match the research topic, which keywords found by 5 (50%) medical/educational consultation articles, 4 (40%) home visits, 4 (40%) reminder articles, and 8 (80%) prolanis exercise articles. Based on the 10 research articles reviewed, there were 4 (80%) medical/educational consultations articles, 3 (75%) home visits articles, 3 (75%) reminder articles, and 8 (100%) prolanis gymnastic articles that related with the blood pressure of hypertension patient’s topic. Meanwhile, there are 1 (20%) medical/ educational consultations article, 1 (25%) reminder article, and 1 (25%) home visits article that are not related to the blood pressure of hypertension patients. Based on the research results, it was concluded that there was a relationship between medical/educational consultations, home visits, reminder, and prolanis exercise to the blood pressure of hypertension patients.